2017
DOI: 10.1007/s13197-016-2472-9
|View full text |Cite
|
Sign up to set email alerts
|

Single step extraction and derivatization of intramuscular lipids for fatty acid Ultra Fast GC analysis: application on pig thigh

Abstract: Two different methods for single step transesterification from pig meat without fat extraction have been tested. Freeze-drying of the meat with and without anhydrous salt, followed by a base-catalyzed transmethylation (KOH/MeOH) was carried out. Both methods were compared with the standard Folch procedure of fat extraction followed by transmethylation. The methods were tested on a complete sample set of biceps femoris of pig thigh, used for the production of dry-cured ham. The set was divided in three subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Lipids were extracted and homogenized with a chloroform/methanol solution using a homogenizer (PT-MR3100 Kinematica, Luzern, Switzerland) [28]. The chloroform was aspirated in the dry bath (Type 16500, USA) at 50 • C using nitrogen gas.…”
Section: Fatty Acid Composition Analysismentioning
confidence: 99%
“…Lipids were extracted and homogenized with a chloroform/methanol solution using a homogenizer (PT-MR3100 Kinematica, Luzern, Switzerland) [28]. The chloroform was aspirated in the dry bath (Type 16500, USA) at 50 • C using nitrogen gas.…”
Section: Fatty Acid Composition Analysismentioning
confidence: 99%
“…Recently emphasis has been placed on animal-derived muscle (meat) fatty acid (FA) analysis, because correct estimation of FA composition is required to define not only nutrient composition of meat, but also to obtain an accurate determination of treatment effects that may alter FA composition [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The most common process to analyse FAs is through the generation of fatty acids methyl esters (FAME) using an initial solvent extraction of lipids, followed by transesterification of the resulting lipids with an alcohol, typically methanol. In recent years, many researches have avoided the solvent extraction step by employing an in-situ transesterification process, in which FAs in a sample are simultaneously extracted and transesterified [4]. Some studies have indicated that this direct process leads to an increase in quantification precision compared with conventional solvent extraction–transesterification procedures [16].…”
Section: Introductionmentioning
confidence: 99%